THE EFFECT OF GIVING ASSIGNMENT METHODS ON STUDENTS’ UNDERSTANDING OF THE SCIENCE CONCEPTS - Maimunah H Daud1; Maria Waldetrudis Lidi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The low score of students’ science learning outcomes at SMPN 1 Ndona during the covid 19 pandemic were caused by the limited interactions between teachers and students. This was supported by limited resources in implementing online learning systems. Giving assignment method was one of methods that could be applied to overcome this problems. The purpose of this study was to determine the effect of giving assignment methods on students’ understanding of science concepts during the Covid-19 pandemic. This study was a type of quantitative research using experimental methods and was carried out at SMPN 1 Ndona in October 2020. The design of this study was a pre-experimental design with one shot case study model. Data were collected through test techniques and the data were analyzed by the formula of t test using SPSS 24. Based on the results of data analysis obtained from 30 students, the value of t count = 31.44 and df = 29 at the significant level ???? = 0.05; it was obtained sig. (2-tailed) 0.000 < 0.05. Thus, H0 was rejected and H1 was accepted. This proved that giving assignment method influenced the students’ understanding on the science concept at grade VII SMPN 1 Ndona.